The Use of “ One Stays Rest Stray” Technique in Teaching Reading Comprehension of Narrative Text at SMK Negeri 3 Parepare - Suci Angela; Rafi'ah Nur; Nasrullah (La Parole : Journal of Language Teaching and Pedagogy, 2019)
Reading comprehension is the most important part of reading ability. However, comprehension in reading cannot be achieved, because students cannot understand the reading material well. In addition, many students find it difficult to understand English texts and are lazy to look for appropriate strategies to collaborate their reading comprehension due to limited access in the neighborhood. This becomes part of the concentration of researchers to carry out this research, when making observations at SMK Negeri 3 Parepare, found the results of students' reading comprehension is still in a fairly problematic condition. The researcher adapted the One stays rest stray strategy as a solution to the lack of students' reading comprehension. In this case, the purpose of this study was to determine whether the one stays rest stray strategy could improve reading comprehension of tenth years students of SMK Negeri 3 Parepare. Researchers used a quasi-experimental method, with the design of two groups of initial and final tests. The research sample consisted of 40 students from two classes as a total population. The results of data analysis showed that students' reading comprehension improved significantly. This is indicated by the average score of the initial test is 37.90 and the final test is 73.85. This shows that the one stays rest stray strategy can be used to improve the reading skills of eighth grade students. After analyzing the data using the t test formula, the results of the t test value at the final test are 5,295. This shows that H1 is accepted and H0 is rejected, and students taught through the one stays rest stray strategy have better improvement than students taught through the self directed learning strategy.